2000
DOI: 10.1042/0264-6021:3490299
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of β-amyloid of the Alzheimer’s and the Dutch-cerebral-haemorrhage types

Abstract: A novel ELISA has been developed which detects oligomerization of beta-amyloid (A beta). Oligomerization, fibrillization and neurotoxicity of native A beta associated with Alzheimer's disease (AD) type has been compared with E22Q A beta (amyloid beta-protein containing residues 1--40 with the native Glu at residue 22 changed to Gln) implicated in Dutch cerebral haemorrhage disease. Solutions of A beta rapidly yield soluble oligomers in a concentration-dependent manner, which are detected by the ELISA, and by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
57
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 38 publications
(2 reference statements)
9
57
1
Order By: Relevance
“…3, we observed that oligomeric A␤-(1-42) inhibited neuronal viability ϳ10-fold more than fibrillar A␤-(1-42) (50% cell viability for oligomeric A␤-(1-42) Ϸ 0.4 M versus 4.0 M for fibrillar A␤-(1-42)), with significant oligomer toxicity exhibited as low as 10 nM. These results are particularly relevant when compared with previous publications that routinely required micromolar concentrations of A␤ to induce neurotoxicity (14,17,18,26,41,50).…”
Section: Resultsmentioning
confidence: 40%
See 4 more Smart Citations
“…3, we observed that oligomeric A␤-(1-42) inhibited neuronal viability ϳ10-fold more than fibrillar A␤-(1-42) (50% cell viability for oligomeric A␤-(1-42) Ϸ 0.4 M versus 4.0 M for fibrillar A␤-(1-42)), with significant oligomer toxicity exhibited as low as 10 nM. These results are particularly relevant when compared with previous publications that routinely required micromolar concentrations of A␤ to induce neurotoxicity (14,17,18,26,41,50).…”
Section: Resultsmentioning
confidence: 40%
“…These mutations induce an increase in the rate of fibril or protofibril formation in A␤- (1-40), respectively, without affecting the generation of A␤ or the A␤(1-42)/A␤(1-40) ratio and actually reduce A␤-(1-42) in transfected cells (31,38,41,42). The increase in protofibril and fibril formation of the mutants under the oligomerforming conditions did not induce a consistent change in neuronal viability.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations